Role of Herbal Immunomodulators in Control of Coccidiosis Disease - Mansoor, Muhammad; Jamil, Muhammad; Ali, Asghar; Shahzad, Haroon; Haq, Rizwan-ul-; Awan, Aftab Ahmad; Gul, Jaweria (Biological Sciences - PJSIR, 2017)
Herbal plants and their derivatives have been utilized since antiquity in the control and management of poultry coccidiosis. The best known herbal plants in use against coccidiosis are corn, wheat bran, rice bran, polysaccharides, soya bean, barley, oat, extracts of grape seed, Dictamnus dasycarpus Turcz, Pulsatilla koreana, Sinomenium acutum, Ulmus macrocarpa, Dichroafe brifuga and other botanical antioxidants which contain many active compounds. These compounds have been found to possess antiprotozoal, anti- parasitic, anti-inflammatory and antioxidant properties. Currently demand and utilization of these aforesaid herbs has increased because these have been proved successful and effective in control of coccidiosis, eco- friendly and economical. The effective potential of these herbals and derivatives to have been reviewed overcome coccidiosis effectively in a better way than other synthetic products against which resistance has been developed.